Studi Banding Penerapan Keadilan Restoratif: Evaluasi Praktik di Indonesia dan Skotlandia - Akbar, Hafiz Prasetia (Pusat Penelitian dan Pengembangan Polri, 2024)
Restorative justice is a growing justice concept being adopted worldwide. The Indonesian National Police and Attorney General have created regulations to ensure legal certainty of its application. However, their implementation has faced a number of impediments. Scotland has been making similar efforts to adopt restorative justice practices. Meanwhile, the implementation of this initiative is supported not just by legislative provisions but also by a thorough action plan. As a result, this study compares Indonesia's progress towards the adoption of restorative justice to Scotland's ongoing efforts in the same arena. This research uses qualitative methodology involving literature review, examination of socio-legal phenomena, and inductive reasoning to draw conclusions. The study's findings show that both Indonesia's police-led conferencing and Scotland's practitioner-led conferencing have advantages and drawbacks. However, Scotland's restorative justice has more involvement in community reconciliation after the conference than Indonesia's pursuit of crime clearance. Furthermore, while both jurisdictions show favourable support in the implementation of restorative justice, Indonesia emphasises macro-level criminal policy and resource conservation, while Scotland emphasises micro-level results like fewer re-offending and victim satisfaction.